2018
DOI: 10.3389/fgene.2018.00437
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of the Goldfish-Like Fish Derived From Hybridization of Female Koi Carp × Male Blunt Snout Bream

Abstract: Goldfish (Carassius auratus var., GF; 2n = 100) is the most popular ornamental fish in the world. It is assumed that GF evolved from red crucian carp (C. auratus red var., RCC; 2n = 100). However, this hypothesis lacks direct evidence. Furthermore, our knowledge of the role of hybridization in the formation of new species is sparse. In this study, goldfish-like fish with twin tails (GF-L; 2n = 100) was produced by self-mating red crucian carp-like fish (RCC-L; 2n = 100) derived from the distant crossing of koi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In a long-term breeding experiment, we found that the GF originated from the distant hybridization of KOC (♀) and BSB (♂) (Wang et al, 2018). We believed that the GF was derived via the route KOC-RCC-GF.…”
Section: Evaluation Of Ka/ks Ratios In Inferred Orthologous Gene Pairmentioning
confidence: 96%
See 3 more Smart Citations
“…In a long-term breeding experiment, we found that the GF originated from the distant hybridization of KOC (♀) and BSB (♂) (Wang et al, 2018). We believed that the GF was derived via the route KOC-RCC-GF.…”
Section: Evaluation Of Ka/ks Ratios In Inferred Orthologous Gene Pairmentioning
confidence: 96%
“…Thus, hybrids could exhibit many advantageous traits, such as rapid growth, strong disease resistance, and strong environmental tolerance (Bartley et al, 2000;Liu et al, 2016). In previous research (Wang et al, 2018), the homodiploid hybrids (RCC-L and GF-L) originated from the distant hybridization of KOC (♀) × BSB (♂) exhibited significant changes in shape. These RCC-L and GF-L had bright black eyes and a white base colour covered with red and yellow patterns (Figure 1).…”
Section: The Significance Of Hybridizationmentioning
confidence: 98%
See 2 more Smart Citations
“…MtDNA recombination was also observed in the F 1 to F 3 generations of a crucian carp-like fish lineage that was derived via the distant cross of female common carp (COC, 2 n = 100) and male blunt snout bream (BSB, 2 n = 48) ( Wang et al, 2019 ). Koi carp, a variety of common carp that is characterized by red or colorful bodies, have the same age of sexual maturity as blunt snout bream ( Wang et al, 2018 ). Blunt snout bream and koi carp are in the same family (Cyprinidae) but different subfamilies (Cultrinae and Cyprinidae, respectively).…”
Section: Introductionmentioning
confidence: 99%